2003
DOI: 10.1254/jphs.93.118
|View full text |Cite
|
Sign up to set email alerts
|

Block by Phytoestrogens of Recombinant Human Neuronal Nicotinic Receptors

Abstract: Abstract. The effects of phytoestrogens on neuronal nicotinic acetylcholine receptor / channels were examined by expressing recombinant channels in Xenopus oocytes. When functional channels were expressed with human a 4 and b2 subuints, daidzein (10 and 100 m M) partially inhibited the ionic current activated by acetylcholine. The current inhibition was also observed when functional channels were expressed with human a3 and b4 subunits or rat homologues. Genistin (100 m M) also inhibited the acetylcholine-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
3
4
0
Order By: Relevance
“…Significantly, we utilized only a single FES device to measure the effect of various regulating drugs such as genistin, daidzein, and tamoxifen on the nAChR activity of multiple SCLC cells, which enabled a statistically meaningful quantitative analysis without errors from device-to-device variations. The results indicate that the treatment of inhibitors such as genistin and daidzein can dramatically reduce Ca 2+ influx in SCLC cells as expected . Furthermore, tamoxifen, which has been known as the antagonist, was found to only partly block the binding of daidzein to nAChRs.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Significantly, we utilized only a single FES device to measure the effect of various regulating drugs such as genistin, daidzein, and tamoxifen on the nAChR activity of multiple SCLC cells, which enabled a statistically meaningful quantitative analysis without errors from device-to-device variations. The results indicate that the treatment of inhibitors such as genistin and daidzein can dramatically reduce Ca 2+ influx in SCLC cells as expected . Furthermore, tamoxifen, which has been known as the antagonist, was found to only partly block the binding of daidzein to nAChRs.…”
supporting
confidence: 64%
“…Phytoestrogens are known as inhibitors that have a high affinity with α4 nAChRs and inhibit the receptors from interacting with nicotine . Thus, when nicotine is added, Ca 2+ influx through α4 nAChRs is blocked and we should observe a reduced overall Ca 2+ influx into the SCLC cell. , In turn, this decrease of membrane depolarization could also reduce the gate-opening of voltage-gated Ca 2+ channels and additional influx of Ca 2+ . In the case of a partial blocking, the quantitative monitoring of electrophysiological responses can enable the quantitative analysis of the effect of drugs.…”
Section: Resultsmentioning
confidence: 94%
“…It has thus been shown that treatment of ovariectomized rats with estrogen upregulated both mRNA and protein of the ␣4 subunit in the hypothalamus [36] and that estradiol potentiated the ␣4␤2nAChR expressed in Xenopus oocytes or human embryonic kidney cells [37]. By contrast phytoestrogens significantly inhibited the function of the ␣4␤2nAChR expressed in X. oocytes [38]. Recent studies by PCR analysis have shown that the ␣4nAChR subunit gene was downregulated in human lung adenocarcinoma tissues, most of which were collected from women [12].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the release of GABA is regulated by α4β2nAChR, which is desensitized in smokers [110,111] and additionally downregulated in PACs by NNK, leading to a deficit in GABA [112]. The desensitization of this receptor is enhanced by estrogens and phyto-oestrogens [113]. The predominance of PAC in women and NNK-induced tumors in OGG knockout female mice may therefore, at least in part, be the result of estrogen impaired α4β2nAChR function.…”
Section: Tobacco-specific Carcinogensmentioning
confidence: 99%